2008
DOI: 10.1007/s00442-008-1012-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of density-dependent individual growth in the persistence of freshwater salmonid populations

Abstract: Theoretical and empirical models of populations dynamics have paid little attention to the implications of density-dependent individual growth on the persistence and regulation of small freshwater salmonid populations. We have therefore designed a study aimed at testing our hypothesis that density-dependent individual growth is a process that enhances population recovery and reduces extinction risk in salmonid populations in a variable environment subject to disturbance events. This hypothesis was tested in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(72 citation statements)
references
References 59 publications
3
68
1
Order By: Relevance
“…With additional assumptions, they have been used to predict larger spatial patterns of biomass distribution or capacity (Grossman et al, 2002;Hayes et al, 2007;Hughes, 1998), but a remaining challenge is linking spatial patterns of growth and survival to population viability (Anderson et al, 2006b;Armstrong and Nislow, 2012;Frank et al, 2011;Locke et al, 2008). Individual-based modeling (IBM) approaches based on the bioenergetics of specific life stages for individual fish have been the most successful at this integration and have shown great utility in river management contexts (Van Winkle et al, 1998;Vincenzi et al, 2008). Most current IBMs are parameter rich, requiring extensive data and/or natural history knowledge of the particular system for calibration (Breckling et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…With additional assumptions, they have been used to predict larger spatial patterns of biomass distribution or capacity (Grossman et al, 2002;Hayes et al, 2007;Hughes, 1998), but a remaining challenge is linking spatial patterns of growth and survival to population viability (Anderson et al, 2006b;Armstrong and Nislow, 2012;Frank et al, 2011;Locke et al, 2008). Individual-based modeling (IBM) approaches based on the bioenergetics of specific life stages for individual fish have been the most successful at this integration and have shown great utility in river management contexts (Van Winkle et al, 1998;Vincenzi et al, 2008). Most current IBMs are parameter rich, requiring extensive data and/or natural history knowledge of the particular system for calibration (Breckling et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…not following extreme events) conditions, but they may be more likely to successfully reproduce when fewer older fish compete for mates. Vincenzi et al [29,39] found in theoretical work that faster growth due to lower density and younger age at reproduction due to size-dependent sexual maturity-or weaker competition for mates-should increase the probability of persistence of marble trout populations affected by extreme events.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of flash floods and debris flows affecting marble trout, survival of fish is thus expected to be largely determined by chance; for However, the conditions created by such extreme events in the years following their occurrence (e.g. greater per capita resources such as food and space due to transient low population density and mobilization of nutrients, fewer older fish) may increase the prevalence of more opportunistic life histories through selection, phenotypic plasticity or changes in population age and size structure [18,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variability exists within fish populations in terms of optimal and critical temperatures for life histories such as growth, survival and reproduction [18], and thus traits related to thermal means and extremes can be selected for [19]. On the contrary, severe floods-especially when swift, aseasonal and with longer recurrence interval than species' generation time [20]-are likely to cause high and largely non-selective mortalities, for example by scouring eggs or killing fish by impact with rocks and boulders [21]. These non-selective population and ( potential) genetic bottlenecks [22] caused by a point extreme are likely to contribute to the erosion of adaptive potential of populations (i.e.…”
Section: Introductionmentioning
confidence: 99%